2007
DOI: 10.1094/pdis-91-10-1363a
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Tomato yellow leaf curl Thailand virus in Taiwan

Abstract: During the 2006 winter and 2007 spring seasons, tomato lines carrying the Ty2 gene, which confers resistance to the Tomato leaf curl Taiwan virus (GenBank Accession No. U88692), showed severe yellowing, leaf curl, and stunting symptoms in several locations in Tainan County, Taiwan. Whiteflies were found to be associated with symptomatic plants, and disease incidences of almost 100% were observed. The presence of a new resistance breaking begomovirus was suspected. Six symptomatic leaf samples of three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…This indicates that the dynamics of tomato‐infecting begomoviruses in Taiwan has changed from ToLCTWV to TYLCTHV and mixed infections of ToLCTWV and TYLCTHV. These dynamics may have been influenced by the release in Taiwan in 2003 of tomato cultivars carrying the Ty‐2 gene which confers resistance to ToLCTWV but not TYLCTHV (Jan et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the dynamics of tomato‐infecting begomoviruses in Taiwan has changed from ToLCTWV to TYLCTHV and mixed infections of ToLCTWV and TYLCTHV. These dynamics may have been influenced by the release in Taiwan in 2003 of tomato cultivars carrying the Ty‐2 gene which confers resistance to ToLCTWV but not TYLCTHV (Jan et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, during the winter of 2006 and spring of 2007, tomato lines carrying the Ty‐2 resistance gene were observed with leaf curl symptoms and molecular identification revealed this to be caused by strains of the bipartite begomovirus species Tomato yellow leaf curl Thailand virus (TYLCTHV). Two TYLCTHV DNA‐A sequences ( and ) were subsequently determined (Jan et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Tomato yellow leaf curl Thailand virus (TYLCTHV) was for the first time reported from Thailand in 1994 (Blawid et al, 2008;Knierim and Maiss, 2007;Rochester et al, 1994;Sawangjit et al, 2005) and then subsequently it spread to Myanmar (Green et al, 2001), south China (Guo et al, 2009;Li et al, 2004) and recently it introduced in Taiwan in 2005 (Jan et al, 2007) where it has changed the dynamics of pre tomato existing begomoviruses as itself a leading tomato-infecting begomovirus; and is causing extensive damage to tomato production in Taiwan (Shih et al, 2010;Tsai et al, 2011). It seems likely that TYLCTHV is more virulent and aggressive with a wider host range (Shih et al, 2010) and outcompetes and replaces Tomato yellow leaf curl Taiwan virus (ToLCTWV), which might be due to more efficient transmission by either indigenous or introduced biotypes of whitefly (Tsai et al, 2011).…”
Section: Effect Of Begomoviruses Movement On Disease Dynamicsmentioning
confidence: 99%
“…TYLCTHV has also been reported to be prevalent in Myanmar, Cambodia, southern China and Taiwan [ 9 12 ]. In Taiwan, TYLCTHV has been found to be so virulent that it can overcome the commonly-deployed Ty-2 -resistant tomato cultivars [ 10 ]. Recent studies have shown that TYLCTHV tends to supplant the local Tomato leaf curl Taiwan virus (ToLCTV) in many parts of Taiwan [ 13 ].…”
Section: Introductionmentioning
confidence: 99%